Environmental costs and benefits of growing Miscanthus for bioenergy in the UK - McCalmont, Jon P. (John Wiley and Sons Inc., 2015)

(untitled) (Glob Change Biol Bioenergy)
Planting the perennial biomass crop Miscanthus in the UK could offset 2–13 Mt oil eq. yr(−1), contributing up to 10% of current energy use. Policymakers need assurance that upscaling Miscanthus production can be performed sustainably without negatively impacting essential food production or the wider environment. This study reviews a large body of Miscanthus relevant literature into concise summary statements. Perennial Miscanthus has energy output/input ratios 10 times higher (47.3 ± 2.2) than annual crops used for energy (4.7 ± 0.2 to 5.5 ± 0.2), and the total carbon cost of energy production (1.12 g CO(2)‐C eq. MJ(−1)) is 20–30 times lower than fossil fuels. Planting on former arable land generally increases soil organic carbon (SOC) with Miscanthus sequestering 0.7–2.2 Mg C4‐C ha(−1) yr(−1). Cultivation on grassland can cause a disturbance loss of SOC which is likely to be recovered during the lifetime of the crop and is potentially mitigated by fossil fuel offset. N(2)O emissions can be five times lower under unfertilized Miscanthus than annual crops and up to 100 times lower than intensive pasture. Nitrogen fertilizer is generally unnecessary except in low fertility soils. Herbicide is essential during the establishment years after which natural weed suppression by shading is sufficient. Pesticides are unnecessary. Water‐use efficiency is high (e.g. 5.5–9.2 g aerial DM (kg H(2)O)(−1), but high biomass productivity means increased water demand compared to cereal crops. The perennial nature and belowground biomass improves soil structure, increases water‐holding capacity (up by 100–150 mm), and reduces run‐off and erosion. Overwinter ripening increases landscape structural resources for wildlife. Reduced management intensity promotes earthworm diversity and abundance although poor litter palatability may reduce individual biomass. Chemical leaching into field boundaries is lower than comparable agriculture, improving soil and water habitat quality.